AYURVEDA: AN INTERNATIONAL OVERVIEW-PART II - Pal, Madhabendra Nath (Medknow Publications & Media Pvt Ltd, 1989)
In the second part of the study the author discusses disease, drug and Ayurvedic theory and practice briefly.